Optimalisasi Pemanfaatan Alat Peraga Matematika Guna Mendukung Proses Deep Learning di Kota Magelang - Rahmawati, Fadhilah; Nurjanah, Arifta; Dwi Pamungkas, Megita; Aldila Krisma, Dita (INCOME: Indonesian Journal of Community Service and Engagement, 2025)
Mathematics learning at the junior high school level still faces challenges, including limited availability of mathematics learning media. This situation does not align with the demands of the deep learning paradigm, which emphasizes in-depth conceptual understanding. This activity aims to optimize the use of teaching aids tailored to students' thinking levels, thereby supporting meaningful learning. Implementation methods included a school needs survey, design and production of teaching aids, and implementation support. Data were collected through observation and questionnaires. Results showed that the use of mathematical teaching aids increased student engagement and interest in learning. Furthermore, students found learning mathematics more engaging. The conclusion of this program is that optimizing utilization has proven effective in supporting interactive, meaningful, and deep learning-oriented learning, making it worthy of recommendation for wider implementation.